Manually Feed NPK Fertigation Improves Growth and Yield of Chili Pepper Hybrids in Ultisol - Herison, Catur; Rustikawati, Rustikawati; Hasanudin, Hasanudin; Suharjo, Usman K.J.; Handajaningsih, Merakati; Nursalim, Nursalim (Akta Agrosia, 2020)
Extending the planting area to a less-fertile soil, such as Ultisols, become inevitable choice to increase the national chili pepper production in Indonesia as this types of soil is the largest part of dry land of Indonesia, about 29.7% or around 51 million ha.  However, efforts to increase its productivity by providing sufficient fertilizers application is most frequently inefficient because in the conventional fertilizer applications, broadcasted fertilizer on the soil bed, are not readily available for the plant as their solubility is limited under the plastic mulch and still in the form of granular until the end of planting season.  Fertigation, therefore, maybe the answer for this problem.  The objective of this study was to determine the best NPK fertigation method on four chili pepper hybrids.  The experiment was conducted in a randomized complete block design with three replication, and the treatments were arranged in a split plot design.  As the main plots were NPK fertigation intensity, i.e. 100%, 75%, 50%, 25% and 0% fertigation with the remnant fertilizers were circularly broadcasted surrounding the plant.  As the subplots were chili pepper hybrids, i.e. ‘Maxima’, H39, H14, and ‘UNIB CHR17’.  The results showed that there was no interaction effect of fertigation intensity indicated that all hybrid genotypes showed similar pattern of responses.  The H39 hybrid had better vegetative growth compared to other hybrids in term of plant height, dichotomous height, stem diameter, number of branches, plant fresh-weight.  Whereas the hybrid cultivar ‘Maxima’ showed the highest yield followed by H14 and cultivar ‘UNIB CHR17’.  The 100% fertigation was the best method of NPK fertilizer application for chili pepper in Ultisols.keywowrd: fertigation, chili pepper, fertilizer application, acidic soil